A Comparison between the Second Korean Working Conditions Survey (KWCS) and the First KWCS - Young Sun Kim; Jungsun Park; Kyung Yong Rhee; Hye Min Kim (Elsevier, 2015)
Background: The study was designed to assess the changes in working conditions through a comparative analysis of the characteristics of working conditions in 2006 and 2010. Methods: We performed a comparative analysis of the data related to the first Korean Working Conditions Survey (KWCS) and the second KWCS in the categories of demographic characteristics, quality of labor, exposure to hazards, and health problems. Results: From our analysis of the demographic characteristics, we saw an increase in labor force participation rate of women and elderly people. As a result of the investigation with regards to working hours, the ratio of employees who worked for ≥ 49 hours per week was decreased and the ratio of employees who worked for ≥ 40 h/wk increased. As for exposure to hazards, exposure to tobacco smoke notably decreased in 2010 compared with 2006. With regards to health problems, there was a sharp increase in the number of people who complained of muscle pain in their arms and legs. Conclusion: KWCS data included many aspects of working conditions as a nationwide sample. In addition, because this is a periodic nationwide survey, the labor force, working hours, harmful factor exposure, and the change in health problems characteristics according to the flow of time could be investigated. The information comparing the main results of the first survey conducted in 2006 and the second survey conducted in 2010 obtained through this study can be used as an important base material for the establishment of the national policy.